KEBIASAAN MAKANAN IKAN TEMBANG Sardinella flmbriata Val. (Fam. Clupeidae) DI PERAIRAN TELUK KENDARI SULAWESI TENGGARA [Study on Food Habits of Fringescale Sardinella, Sardinellafimbriata Val. (Fam. Clupeidae) in Kendari Bay, Southeast Sulawesi] - Asriyana Asriyana; Sulistiono Sulistiono; M. F. Rahardjo (Jurnal Iktiologi Indonesia, 2004)
A study on food habit of Fringescale Sardinella, Sardinella fimbriata Val. in Kendari Bay was conducted from March to December 2003. This research aims to observe food habits and feeding periodicity of the fish and relation of the food habits and plankton, food habit was determined by using Index of Relative Importance method. Result of the study indicates that fringescale Sardinella is plankton feeder and taking its food by filtering. Important diet of fish is Bacillariophyceae and Crustacea.